Catatan perjalanan seni Zurinah Hassan : penerima anugerah penulisan S.E.A 2004 - Zurinah Hassan, 1949- Dato' (Kuala Lumpur : Institut Terjemahan & Buku Malaysia : PENA, 2014)
Autobiography and creative writing process of Zurinah Hassan, a Malaysian woman writer.
In Malay.
Includes bibliographical references (pages 143-146).
Keywords: Zurinah Hassan, -- 1949-; Authors, Malay -- Biography